2004
DOI: 10.1038/nm983
|View full text |Cite
|
Sign up to set email alerts
|

A MARCKS-related peptide blocks mucus hypersecretion in a mouse model of asthma

Abstract: Mucus hypersecretion is a crucial feature of pulmonary diseases such as asthma, chronic bronchitis and cystic fibrosis. Despite much research, there is still no effective therapy for this condition. Recently, we showed that the myristoylated, alanine-rich C-kinase substrate (MARCKS) protein is required for mucus secretion by human bronchial epithelial cells in culture. Having synthesized a peptide corresponding to the N-terminal domain of MARCKS, we now show that the intratracheal instillation of this peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
163
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(171 citation statements)
references
References 18 publications
7
163
0
1
Order By: Relevance
“…4 A and B, benzbromarone (10 μM) applied on the apical side of IL-13-treated NHBE cells effectively blocked the ATP (100 μM)-induced CaCC current in Ussing chamber recordings (1.137 ± 0.1301 vs. 3.099 ± 0.4721, n = 4, P = 0.0071). Similar to previous studies (45,46), we observed a depletion of the mucin stores in mucous cells after exposing the apical side of NHBE cells to ATP for 30 min (Fig. 4 C and E).…”
Section: Tmem16a Is Preferentially Expressed In Secretory Cells In Assupporting
confidence: 91%
“…4 A and B, benzbromarone (10 μM) applied on the apical side of IL-13-treated NHBE cells effectively blocked the ATP (100 μM)-induced CaCC current in Ussing chamber recordings (1.137 ± 0.1301 vs. 3.099 ± 0.4721, n = 4, P = 0.0071). Similar to previous studies (45,46), we observed a depletion of the mucin stores in mucous cells after exposing the apical side of NHBE cells to ATP for 30 min (Fig. 4 C and E).…”
Section: Tmem16a Is Preferentially Expressed In Secretory Cells In Assupporting
confidence: 91%
“…Indeed, it is possible that mucin hypersecretion per se is beneficial to the host, increasing the capacity to trap and clear inhaled foreign materials. Animal models of mucin hypersecretion, e.g., ovalbumin-sensitized mice (13) and the βENaC transgenic (14) mouse models, exhibit muco-obstructive airway disease associated with inflammatory cell infiltrates but these models have not permitted dissection of the relative roles for mucin hypersecretion vs. inflammation in disease pathogenesis. The increasing interest in mucin hypersecretion as a therapeutic target argues for studies designed to understand the role of mucin hypersecretion in disease pathogenesis.…”
mentioning
confidence: 99%
“…7A) and is supported by inhibited apoE secretion by the peptide inhibitor, BIO-11000. MARCKS regulates the hypersecretion of mucus in respiratory diseases, such as asthma and cystic fibrosis (70,81). Phosphorylation of MARCKS allows movement to the cytoplasm, binding to chaperone HSP70, which engages the cysteine string protein located on the surface of the secretory vesicles containing mucin (69,82).…”
Section: Discussionmentioning
confidence: 99%